TREATMENT OF SELF-LEARNING IN THE CONCEPT OF LIFELONG LEARNING (Annual of the Faculty of Philosophy in Skopje, 2012)
The presence, with all the changes that is bringing in different areas of life and work is demanding the needfor continuing learning and education. That means that the contemporary system of education should and must be built on a new type of learning - learning how to learn or self-learning.The appearance of self-learning can be seen as a reaction to the changes in post-industrial society. Actually, it is a responce of one societal and political question: Does our youth possesses enough knowledge, skills and attitudes neededfor productive life in a post-industrial society?Self-learning per se is an answer to this question, because it gives great autonomy to individuals and is inspiring power in their lives - personal, educational and civic.In this kind of educational conditions it is taken in to recons idiration the still present condition of “ encyclopedian knowledge ”, vis ά vis afirmative need of the students of all levels of education to learn about the methods and techniques of self-learning.The lack of curricula that encompasses elements of self-learning, lack of teacher s manuals that would help them to qualify students with this type of learning, as well as non sufficient prepareness of teachers to use innovative teaching methods and techniques - are common obstacle that is still present in educational systems of many countries, including ours.Self-learning, slowly but safely should become part of every modern system of education, allowing children and adults to become navigators of their own education and learning as well as enabling them to encounter the changes of the knowledge-based society.
Keywords: self-learning; lifelong learning; labor market; knowledge-based society; competencies